DETERMINANTS OF BUYING BEHAVIOR OF CONSUMERS TOWARDS E-VEHICLES - L, Smitha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of the study was to examine customer perceptions of electric vehicles (EVs) and evaluate the factors influencing their decision to purchase one. The survey also aimed to ascertain the opinions of consumers in Bengaluru District regarding electric vehicles. Using a descriptive study design, a quantitative research approach was applied. Data was gathered by distributing a questionnaire to consumers of e-vehicles. The sample consisted of about 192 respondents and was selected by convenience sampling techniques. According to the study's findings, consumer’s expected factors like reducing air pollution and greenhouse gas emissions, gender, refueling habits, the impact of government incentives and financial gains, Innovative Behavior, Media and Peer Influence, consumer serving as a source of information, affordability—both in terms of price and vehicle range—and Product Design are all positively influence with consumers' propensity to purchase E-vehicles. Technological elements that positively influencing with consumers' favorable perceptions of purchasing E-vehicles include Innovations and Invention, advancements in battery technology, price premium reductions, superior e-vehicle service, No noise pollution, Low maintenance cost , and energy independence through a decrease in oil imports.